P19 Evidence for histological lesions precursor to intestinal-type sinonasal adenocarcinoma. Issue 5 (May 2015) - Vivanco, B.; López-Hernández, A.; García-Inclán, C.; Costales, M.; López, F.; Llorent, J.L.; Hermsen, M.
<x xml:space="preserve">Abstract</x> Background Intestinal-type sinonasal adenocarcinomas (ITAC) are rare tumors, related to occupational exposure to wood and leather dust. Clinical symptoms are often indistinguishable from symptoms of patients with benign sinonasal disease, and as a consequence, patients frequently present with advanced-stage tumors. Multistep carcinogenesis through various histological changes accompanied by accumulating genetic alterations has not been demonstrated for ITAC. The aim of this study was to identify histological changes precursor to ITAC that may be useful for early detection for tumors in individuals at risk. Material and methods H&E stained paraffin sections from mucosa adjacent to primary tumor or recurrence of 136 patients with ITAC were evaluated for the presence of respiratory or olfactory epithelium, dysplasia, cuboid metaplasia, squamous metaplasia, and cylindrocellular hyperplasia. Protein expression of differentiation markers CK7, CK20, CDX2, B-III tubulin, Lysozyme, MUC2 and MUC5, and cancer-related genes B-catenin, p53, p16 and Cox2 were analyzed by immunohistochemistry. Results Our preliminary data revealed cuboid metaplasia in more than half of the cases, while intestinal metaplasia and dysplasia, accompanied by a switch to CK7−/CK20+/CDX2+ and in some cases p53/Cox2 expression, occurred in approximately 10–15%. Discussion Possible lesions precursor to ITAC were found infrequently however it may be speculated that these lesions often become destroyed by the growth of the ITAC tumor mass. Therefore we suggest that histological evaluation aided by CK20 and perhaps other biomarkers may be used for screening individuals at risk.